Ophthalmic services in Shanghai 2017: a cataract-centric city-wide government survey - Xiangjia Zhu; Yu Du; Wenwen He; Jinhui Dai; Minjie Chen; Peijun Yao; Han Chen; Hui Ren; Yuan Fang; Shensheng Tan; Yi Lu (BMC, 2021)
Abstract Background Demand for eye care has increased in recent decades in China due to rapid socioeconomic development and demographic shift. Knowledge of output and productivity of ophthalmic services would allow policymakers to optimize resource allocation, and is therefore essential. This study sought to map the landscape of ophthalmic services available in Shanghai, China. Methods In 2018, a government-led survey was conducted of all 86 tertiary/secondary hospitals and five major private hospitals providing eye care in Shanghai in the form of electronic questionnaire, which encompassed ophthalmic services (outpatient and emergency room [ER] visit, inpatient admissions, and surgical volume) and service productivity in terms of annual outpatient and ER visits per doctor, inpatient admissions per bed, and surgical volume per doctor. Comparisons were made among different levels of hospitals with categorical variables tested by Chi-square analysis. Results The response rate was 85.7%. The Eye and Ear, Nose, and Throat (EENT) Hospital was the largest tertiary specialty hospital, and alone contributed to the highest 21.0% of annual ophthalmic outpatient and ER visits (visits per doctor: 5460), compared with other 26 tertiary hospitals, 46 secondary hospitals and five private hospitals (visits per doctor: 3683, 4651 and 1876). The annual inpatient admission was 20,103, 56,992, 14,090, and 52,047 for the EENT Hospital, all the other tertiary hospitals, secondary hospitals and five private hospitals, respectively. Turnover rates were highest for the EENT Hospital and private hospitals. The average surgical volume at the EENT Hospital was 72,666, exceeding that of private (15,874.8) and other tertiary hospitals (3366.7). The EENT Hospital and private hospitals performed 16,982 (14.2%) and 55,538 (46.6%) of all cataract surgeries. Proportions of both complicated cataractous cases and complicated cataract surgeries at the EENT Hospital was the highest, followed by other tertiary and secondary/private hospitals (P < 0.0001). Conclusions In Shanghai, public providers dominate ophthalmic services especially for complicated cases, with almost one fifth of services provided by the EENT Hospital alone, while private sectors, though not large in number, still effectively help meet large proportions of eye care demand. Optimization of hierarchical medical system is warranted to improve the efficiency and standardization of ophthalmic services.